Isoperimetric inequalities in unbounded convex bodies - Leonardi, Gian Paolo; Ritoré, Manuel; Vernadakis, Efstratios (Memoirs of the American Mathematical Society, 2022)
We consider the problem of minimizing the relative perimeter under a volume constraint in an unbounded convex body